TECHNOLOGICAL INNOVATIONS FOR ENHANCING ENGLISH VOCABULARY ACQUISITION - Turdiyeva Zahro Mirsoliyevna (PEDAGOGS, 2025)
This paper explores the integration of technology in English vocabulary acquisition and its impact on language learning outcomes. The rapid advancement of digital tools has transformed traditional learning environments, providing learners with interactive and personalized platforms for vocabulary development. The study examines key technological applications such as mobile apps, gamified learning tools, artificial intelligence-driven platforms, and online resources that contribute to vocabulary enhancement. The findings highlight how technology facilitates engagement, motivation, and long-term vocabulary retention, offering new possibilities for language educators and learners alike.